Postmastectomy radiotherapy in T1-2 patients with one to three positive lymph nodes – Past, present and future. (December 2019) - Kaššák, Filip; Rossier, Christine; Picardi, Cristina; Bernier, Jacques
Abstract: Past: The role of post-mastectomy radiotherapy (PMRT) in patients with tumor <5 cm and one to three positive lymph nodes after axillary dissection (ALND) is vigorously debated. Initial doubts over the efficacy and safety of PMRT in these patients were partially overcome by improvement in technology and systemic treatments. Several randomized controlled clinical trials confirmed benefit of PMRT in N1 patients, which were meta-analyzed by the Early Breast Cancer Trialists' Collaborative Group (EBCTCG). This meta-analysis provides the sole high-level evidence to guide clinical decision-making. Present: Nevertheless, concerns have been evoked around these results, most notably concerning the patient selection bias and the era in which the patients were treated. More recent studies, albeit retrospective, are in contrast with this level I evidence, unequivocally reporting inferior recurrence rates in control arms than those of the EBCTCG meta-analysis. Taken together, these results suggest that one solution would not fit all N1 patients and that patient selection for PMRT shall be stratified upon risks factors. Most prominent of such factors identified are: patient age; number and ratio of positive lymph nodes; histological features such as lymphovascular invasion; and hormone receptor expression. Future: A prospective randomized controlled trial SUPREMO will release its final results in 2023 and shed light onto the subject. Genomic tumor cell profiling will likely provide further guidelines in terms of risk stratification. SUPREMO translational sub-study will also offer material for genomic analyses. A cross-field tendency to forgo nodal dissection in favor of sentinel lymph node biopsy followed by nodal irradiation might eventually render the question of PMRT indication after ALND irrelevant. Highlights: Current level I evidence speaks in favor of PMRT in all node-positive patients. More recent retrospective reports do not show survival benefit after PMRT. With sentinel node biopsy, nodal field irradiation will become more common. Question of indication may be replaced by a question of chest-wall inclusion. Cancer genome analyses will guide clinical decisions, including indication to PMRT.